Use of Concept Mapping as an Innovative Teaching-learning Strategy in Mathematics - Fatima, Roohi (JOURNAL OF INDIAN EDUCATION, 2020)
‘If I had to reduce all of educational psychology to just one principle, I would say this: The most important single factor influencing learning is what the learner already knows. Ascertain this and teach him accordingly’ are the famous words of Ausubel. For this, to help students in making conceptual connections, a technique called ‘Concept Mapping’ was evolved by Novak (1983). In this article, the author attempts to find out whether concept mapping can be used to facilitate the teaching-learning process of mathematics or not? This article is research based. The author, who is a teacher educator, gave an assignment to her B.Ed. students (pedagogy of mathematics) to teach at least one topic or unit during their internship program with the help of technique of Concept Mapping. In this article, she discusses the effectiveness of concept mapping in the teaching-learning process of Mathematics by giving a practical based example of a unit of mathematics of class VIII by using Concept Mapping as a teaching-learning strategy. In the end of this article, she summarises the observation of her students under the heading of “Concept Map as an Evaluation Tool”